1976
DOI: 10.1051/radiopro/19761101035
|View full text |Cite
|
Sign up to set email alerts
|

Étude comparée de la fixation et de la désorption du zinc 65 par un mollusque marin (Mytilus galloprovincialis LmK) et un mollusque dulcicole (Unio requieni Michaud)

Abstract: The kinetics of zinc 65 contamination and distribution was studied in two species of mollusks: a salt water (Mytillus galloprovincialis LmK) and a fresh water (Unio requieni Michaud) species. After 50 days the concentration factor was approximately 500 for Unio requieni, but only 30 for Mytilus galloprovincialis on the 31st day of contamination. Radionuclide retention was essentially localized in the internal organs: 82.5 p. cent for Unio requieni, and 68.1 p. cent for Mytilus galloprovincialis. Zinc 65 desorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1980
1980
1996
1996

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This model can also explain the different excretion rates for zinc in Mytilus reported by previous workers. Thus in whole animals, components with half-lives of < 1 day, 3-4 days and 48-60 days were reported by Van Weers (1973); 5 and 130 days (Foulquier & Baudhuin, 1976); 76 days (Young & Folsom, 1967) and 130 days (Seymour & Nelson, 1973). Both Van Weers (1973) and Keckes et al (1968) found that the relative contribution of these components varied with the length of the uptake periods, the short-lived components only making a significant contribution to the percentage excreted after brief exposure periods (less than 2 weeks).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…This model can also explain the different excretion rates for zinc in Mytilus reported by previous workers. Thus in whole animals, components with half-lives of < 1 day, 3-4 days and 48-60 days were reported by Van Weers (1973); 5 and 130 days (Foulquier & Baudhuin, 1976); 76 days (Young & Folsom, 1967) and 130 days (Seymour & Nelson, 1973). Both Van Weers (1973) and Keckes et al (1968) found that the relative contribution of these components varied with the length of the uptake periods, the short-lived components only making a significant contribution to the percentage excreted after brief exposure periods (less than 2 weeks).…”
Section: Discussionmentioning
confidence: 73%
“…Its radioisotope, the neutron-induced radionuclide 65 Zn, is also released into the sea in significant quantities. Many radiological studies have therefore been carried out both on the uptake of 65 Zn by Mytilus (Boroughs, Chipman & Rice, 1957;Brooks & Rumsby, 1965;Chipman, Rice & Price, 1958;Kameda, Shimizu & Hiyama, 1968;Keckes, Ozretic & Krajnovic, 1969;Pentreath, 1973;Van Weers, 1973) and its loss from contaminated animals (Foulquier & Baudhuin, 1976;Keckes, Ozretic & Krajnovic, 1968;Seymour & Nelson, 1973'•> Van Weers, 1973Young & Folsom, 1967). Other studies have been oriented towards the use of Mytilus as an indicator organism by comparison of water and animal zinc concentrations at different collection sites (e.g.…”
Section: Introductionmentioning
confidence: 99%